IS KIN SELECTION INVOLVED IN THE EVOLUTION OF WARNING COLORATION - Guilford, T (1985)
Kin selection is often though to be important or even necessary for the evolution of warning coloration. Kin selection however has often been invoked erroneously, and has been confused with a second but distinct effect of family grouping-production of a local abundance of similar phenotypes-which may be important during the initial evolution of traits which have density-dependent benefit. Separate discussion is made of the evolution of warning coloration in an already distasteful species, and the joint evolution of warning coloration and distastefulness. In both cases warning coloration is considered to be a green beard altruism trait, and in the first case it is uncheatable. Where it is uncheatable, warning colour altruism is likened to mutualism, and it is argued that classical kin selection cannot be involved in its evolution.-Author